(untitled) (Journal of the College of Basic Education, 2022)
Al-Wasiti’s drawings, with their formative characteristics, are important in deepening the connection between them and the achievements of contemporary Iraqi art, whose influence has become clear on some Iraqi artists through the drawings of their contemporary paintings. I helped in this, and what are the most famous artists influenced by the formative characteristics of Al-Wasiti’s drawings?